Electronic cigarette use among Italian smokers: patterns, settings, and adverse events. Issue 3 (June 2020) - Gallus, Silvano; Borroni, Elisa; Liu, Xiaoqiu; Carrozzi, Laura; Dalla Pietra, Gianfranco; Eslami Varzaneh, Shokoofe; Harari, Sergio; Inciso, Giovanni; Martucci, Paola; Papale, Maria; Pistelli, Francesco; Polla, Biagio; et al.
Objective: Information is scanty on the patterns and settings of electronic cigarette use and on its possible adverse events. To fill the knowledge gap on these issues, we conducted a survey among ever-smokers attending smoking cessation services (SCS) in Italy. Methods: In 2016–2018, we enrolled 395 ever-smokers aged ⩾18 years who were current or former electronic cigarette users in 12 SCS from northern, central, and southern Italy. Results: In all, 12.4% of ever smokers were regular, 9.4% occasional, and 78.2% past users of electronic cigarettes. Of all users, 93.8% consumed electronic cigarettes with nicotine, 95.9% used refillable devices, and 76.6% purchased electronic cigarette devices or liquids in vape shops. The mean duration of use was 3.7 months and the mean number of puffs per day was 86. Among users, 71.5% used electronic cigarettes in at least 1 smoke-free indoor environment, 53.7% in workplaces, 49.5% in restaurants and bars, 33.5% in train/metro stations or airports, and 18.4% in public transports. The use of electronic cigarettes in smoke-free environments significantly decreased with age and increased with duration of use and nicotine dependence. In our sample, 47.1% reported at least 1 adverse event attributable to electronic cigarette use: 19.5% dry cough, 12.0% dry mouth, 7.6% throat or mouth irritation, and 6.8% sore throat. Conclusion: In Italy, most conventional cigarette smokers use electronic cigarettes where smoking conventional cigarettes is prohibited. About half of users reported 1 or more symptoms attributable to electronic cigarettes, despite the relatively short duration of use.